Case report: Intrathecal baclofen therapy improved gait pattern in a stroke patient with spastic dystonia - Kim, Kyung Min; Lee, Tae Kwon; Lee, Su Min; Chang, Won Seok; Lee, Su Ji; Hwang, Jihye; Cho, Sung-Rae (Frontiers in Neurology, 2024)
Background Intrathecal baclofen (ITB) therapy, a viable alternative for unsuitable candidates of conventional spasticity medications, is a preferred method of administration over the oral route. Owing to its enhanced bioavailability, ITB ensures a more effective delivery at the target site. Objective There is a lack of conclusive evidence regarding the use of ITB treatment in managing ambulatory patients with spastic dystonia. Before ITB pump implantation, patients commonly undergo an ITB bolus injection trial to rule out potential adverse reactions and verify the therapeutic effects on hypertonic issues. In this report, we highlight a case of spastic dystonia, particularly focusing on an ambulatory patient who demonstrated significant improvement in both the modified Ashworth scale (MAS) score and gait pattern following the ITB injection trial. Case report This case report outlines the medical history of a 67-year-old male diagnosed with left-side hemiplegia and spastic dystonia, resulting from his second episode of intracranial hemorrhage in the right thalamus. An ITB injection trial was initiated because the patient was not suitable for continued botulinum toxin injections and oral medications. This was due to the persistent occurrence of spastic dystonia in both the upper and lower extremities. The patient underwent a four-day ITB injection trial with progressively increasing doses, resulting in improved MAS scores and gait parameters, including cadence, step length, step time, stride length, and stride time were increased. Particularly, kinematic gait analysis demonstrates a substantial improvement of increased knee flexion in the swing phase in stiff knee gait pattern. These findings indicated a gradual reduction in spasticity-related symptoms, signifying the positive effect of the ITB injection trial. The patient eventually received an ITB pump implantation. Conclusion In this post-stroke patient with spastic dystonia, ITB therapy has demonstrated effective and substantial management of spasticity, along with improvement in gait patterns.